The learning of veterinary students during practical ultrasound exercises - Müller, Anna (Improving University Science Teaching and Learning, 2023)
This report concerns a part of the course Veterinary Imaging1, which a mandatory course in the Master of Veterinary Medicine curriculum. First, the course is briefly introduced. Then a background for the project is given, based on current literature, qualitative interviews and previous student evaluations. This information forms the basis of a number of interventions that have been introduced in the course. Finally, qualitative feedback from students who took the course, and a discussion with the course responsible are used to evaluate and discuss the effect of the implemented interventions.